Improving The Capital Management System For Micro Small And Medium Enterprises On The Quality Of Human Resources - Iyan Sugiana; Agus Koni; Wawan Kurniawan (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the important pillars in the Indonesian economy. MSMEs contribute greatly to the community's economy and employment. However, MSMEs in Indonesia still face various challenges, one of which is the management of business capital that is not optimal. This causes the low quality of human resources (SDI) in MSMEs. This study was conducted to analyze how the relationship between the business capital management system and the quality of human resources (SDI). The type of research used is qualitative, with interview research methods on participants, namely MSME and SDI actors in it. The results showed that there is a positive relationship between the business capital management system and the level of quality of human resources, where with a good capital management system will improve the quality of human resources in the business and vice versa if the level of quality of human resources in the business is better it will increase business development, therefore the role of the government is very influential on this condition where the government can provide training and guidance related to human resources so that their knowledge and skills increase related to the capital management system and human resource performance (SDI).